The influence of notch connection location on the short-term behaviour of timber-concrete composite beams, modelling of TCC beams and research for optimal locations, a numerical study (Fracture and Structural Integrity, 2023)
Timber-concrete composite beams, known as TCC beams, have been widely used in rehabilitation or in new buildings where several types of connections are commonly inserted to ensure partial composite action between the timber joist and the concrete slab. The notched connections represent an effective system due to their strength and ductility and it is simple to cut from timber joists. As a result, a small number is needed for the composite beam to achieve high performance in terms of bending stiffness and load-carrying capacity.This paper aims to develop a FE model for TCC beams with notched connections. It considers realistic interactions between different components.The developed FE model can satisfactorily predict the full range load-mid-span deflection curves and the failure mechanisms.The predictions agree very well with the experimental results reported in the literature, including the stiffness and the load-carrying capacity.After the validation, a numeric study was established, it aimed to research the optimal location of a notch connection between different proposed locations, to figure out which place must be installed to ensure high performance of the TCC beams.As a result of this study, the notch installed at location P3000 was found to be the optimal location to assure the highest bending stiffness. While the maximum carrying capacity was achieved at location P3750.
Keywords: Timber-concrete composite; Notch connection; Notch Location; Optimal Location; Finite element analysis